PENGARUH JENIS KAIN TERHADAP HASIL BAJU KURUNG BASIBA UNTUK ANAK USIA DINI - Novryani, Hellen; Suci, Puji Hujria (Gorga : Jurnal Seni Rupa, 2024)
Baju Kurung Basiba as the identity of Minangkabau women became one of the Minangkabau cultural properties that began to be applied to various levels of education in accordance with the direction of the Governor of West Sumatra. Kurung Basiba clothes are loose and contain many values and expectations aimed at Minangkabau women, so that every generation should know, understand, and love Minangkabau culture will be effective if applied at the education level starting from early childhood. Therefore, it is necessary to pay attention to the manufacture of Kurung Basiba clothes for early childhood in accordance with their needs who use a lot of physical activity in educational activities. Therefore, this study aims to explain the type of fabric that is suitable for early childhood according to their needs and activities in kindergarten. This research uses an experimental method, namely an experiment on three types of fabrics that will be tested for feasibility by two experts from children's fashion lecturers to assess the feasibility of the Kurung Basiba clothes that have been made. The results of the study were divided into three categories, namely; The manufacture of Kurung Basiba clothes uses premium combed cotton, premium oxford cotton fabric and premium original toyobo fabric and shows that original toyobo fabric has the highest feasibility rate, namely the percentage of 78.7% with the decent category, while the second is premium combed cotton with a percentage of value of 74.3% with the decent enough category and the third is premium oxford catton fabric with a percentage of 64.1% with the less decent category. This study emphasizes the need to consider the selection of Kurung Basiba clothing fabric material for early childhood.Keywords: fabric type, Basiba kurung shirt, early childhoodAbstrakBaju Kurung Basiba sebagai identitas perempuan Minangkabau menjadi salah satu kekayaan budaya Minangkabau yang mulai diterapkan pada berbagai jenjang pendidikan sesuai dengan arahan Gubernur Sumatera Barat. Baju Kurung Basiba yang longgar dan mengandung banyak nilai dan harapan yang ditujukan kepada perempuan Minangkabau, sehingga selayaknya setiap generasi mengetahui, memahami, dan mencintai budaya Minangkabau akan efektif jika diterapkan dijenjang pendidikan mulai dari anak usia dini. Oleh karena itu, perlu diperhatikan pembuatan baju Kurung Basiba untuk anak usia dini sesuai dengan kebutuhannya yang banyak menggunakan aktivitas fisik pada kegiatan pendidikan. Oleh sebab itu, penelitian ini bertujuan untuk memaparkan jenis kain yang sesuai untuk anak usia dini sesuai dengan kebutuhan dan aktifiktas mereka dibangku Taman Kanak-Kanak. Penelitian ini menggunakan metode eksperimen yakni percobaan terhadap tiga jenis kain yang akan diuji kelayakannya oleh dua ahli dari dosen busana anak untuk menilai kelayakan dari baju Kurung Basiba yang telah dibuat. Hasil penelitian dibagi kedalam tiga kategori yakni; pembuatan baju Kurung Basiba menggunakan bahan katun combed premium, kain katun oxford premium dan kain toyobo original premium dan menunjukkan bahwa kain toyobo original memiliki tingkat kelayakan paling tinggi yakni jumlah persentase 78,7% dengan kategori layak, sementara yang kedua adalah katun combed premium dengan persentase nilai 74,3% dengan kategori cukup layak  serta yang ketiga adalah kain catton oxford premium dengan persentase 64,1% dengan kategori kurang layak. Penelitian ini menekankan perlunya mempertimbangkan pemilihan bahan kain baju Kurung Basiba untuk anak usia dini.Kata kunci: jenis kain, baju kurung Basiba, anak usia dini. Authors:Hellen Novryani : Universitas Negeri PadangPuji Hujria Suci : Universitas Negeri Padang ReferencesAlfarist, S. Z., & Ratuannisa, T. (2024). Education Of Basic Geometric Shapes In Children Aged 5-6 Years Through Ready To. 7, 37“52. Https://Doi.Org/10.25105/Jsrr.V7i1.19086Andanari, R., Kahdar, K., & Riyadi, S. (2020). Standardisasi Desain Seragam Sekolah Siswa Taman Kanak-Kanak. Jurnal Sosioteknologi, 18(3), 422“432. Https://Doi.Org/10.5614/Sostek.Itbj.2019.18.3.9April, E., Ernawati, & Adriani. (2015). Studi Tentang Busana Tradisional Pasumandan Padang.Fitri, Y., & Nelmira, W. (2024). Harau Kabupaten Lima Puluh Kota Design And Meaning Of Penghulu Clothing In Nagari Taram , Harau , Lima Puluh Kota Regency. 13(September 2023).Imelda, D. (2016). Revitalisasi Baju Kuruang Basiba Minangkabau. Ekspresi Seni, 18(2). Https://Doi.Org/10.26887/Ekse.V18i2.92Kartono, G., Sugito, S., & Azis, A. C. K. (2021). Pengembangan Bahan Ajar Bermuatan Lokal Batak Untuk Sekolah Menengah Di Kota Medan. Gorga¯: Jurnal Seni Rupa, 10(1), 215. Https://Doi.Org/10.24114/Gr.V10i1.25971Mayliana, E. (2019). Penciptaan Busana Anak Dengan Menerapkan Teknik Substraction Cutting. Corak, 8(1), 49“56. Https://Doi.Org/10.24821/Corak.V8i1.2690Murdiyanto, E. (2020). Metode Penelitian Kualitatif (Sistematika Penelitian Kualitatif). In Bandung: Rosda Karya.Mustika, W. G., & Budiwirman, B. (2019). Analisis Fungsi Dan Makna Suntiang Dalam Pakaian Adat Minangkabau. Gorga¯: Jurnal Seni Rupa, 8(2), 315. Https://Doi.Org/10.24114/Gr.V8i2.14712Rahmadani, S., & Hasrul, H. (2021). Program Dinas Kebudayaan Sumatera Barat Dalam Melestarikan Budaya Minangkabau. Journal Of Civic Education, 4(2), 163“172. Https://Doi.Org/10.24036/Jce.V4i2.526Rujainah, S., Mukhirah, & Novita. (2021). Desain Seragam Paud Kasih Bunda Di Kecamatan Sultan Daulat Kota Subulussalam. November, 56“68.Siti Nur Hayati, & Putro, K. Z. (2021). Bermain Dan Permainan Anak Usia Dini. Generasi Emas, 4(1), 52“64. Https://Doi.Org/10.25299/Jge.2021.Vol4(1).6985Suci, P. H., Puspaneli, & Yupelmi, M. (2023). Training Decorating Accessories Veil And Family To Increase Revenue And Tourism In Kenagarian Payo Lubuk Sikarah District City Of West Sumatra Solok. International Journal Of Educational Dynamics, Vol. 1 No.Sudjana. (2010). Metode Statistika. Pt Arsita Bandung.Syafitri, P. R., Widihastuti, & Jerusalem, M. A. (2021). Pewarnaan Alam Daun Ketapang Pada Pada Produk Upcycle Busana Anak. 2“5.Alfarist, S. Z., & Ratuannisa, T. (2024). Education Of Basic Geometric Shapes In Children Aged 5-6 Years Through Ready To. 7, 37“52. Https://Doi.Org/10.25105/Jsrr.V7i1.19086Andanari, R., Kahdar, K., & Riyadi, S. (2020). Standardisasi Desain Seragam Sekolah Siswa Taman Kanak-Kanak. Jurnal Sosioteknologi, 18(3), 422“432. Https://Doi.Org/10.5614/Sostek.Itbj.2019.18.3.9April, E., Ernawati, & Adriani. (2015). Studi Tentang Busana Tradisional Pasumandan Padang.Fitri, Y., & Nelmira, W. (2024). Harau Kabupaten Lima Puluh Kota Design And Meaning Of Penghulu Clothing In Nagari Taram , Harau , Lima Puluh Kota Regency. 13(September 2023).Imelda, D. (2016). Revitalisasi Baju Kuruang Basiba Minangkabau. Ekspresi Seni, 18(2). Https://Doi.Org/10.26887/Ekse.V18i2.92Kartono, G., Sugito, S., & Azis, A. C. K. (2021). Pengembangan Bahan Ajar Bermuatan Lokal Batak Untuk Sekolah Menengah Di Kota Medan. Gorga¯: Jurnal Seni Rupa, 10(1), 215. Https://Doi.Org/10.24114/Gr.V10i1.25971Mayliana, E. (2019). Penciptaan Busana Anak Dengan Menerapkan Teknik Substraction Cutting. Corak, 8(1), 49“56. Https://Doi.Org/10.24821/Corak.V8i1.2690Murdiyanto, E. (2020). Metode Penelitian Kualitatif (Sistematika Penelitian Kualitatif). In Bandung: Rosda Karya.Mustika, W. G., & Budiwirman, B. (2019). Analisis Fungsi Dan Makna Suntiang Dalam Pakaian Adat Minangkabau. Gorga¯: Jurnal Seni Rupa, 8(2), 315. Https://Doi.Org/10.24114/Gr.V8i2.14712Rahmadani, S., & Hasrul, H. (2021). Program Dinas Kebudayaan Sumatera Barat Dalam Melestarikan Budaya Minangkabau. Journal Of Civic Education, 4(2), 163“172. Https://Doi.Org/10.24036/Jce.V4i2.526Rujainah, S., Mukhirah, & Novita. (2021). Desain Seragam Paud Kasih Bunda Di Kecamatan Sultan Daulat Kota Subulussalam. November, 56“68.Siti Nur Hayati, & Putro, K. Z. (2021). Bermain Dan Permainan Anak Usia Dini. Generasi Emas, 4(1), 52“64. Https://Doi.Org/10.25299/Jge.2021.Vol4(1).6985Suci, P. H., Puspaneli, & Yupelmi, M. (2023). Training Decorating Accessories Veil And Family To Increase Revenue And Tourism In Kenagarian Payo Lubuk Sikarah District City Of West Sumatra Solok. International Journal Of Educational Dynamics, Vol. 1 No.Sudjana. (2010). Metode Statistika. Pt Arsita Bandung.Syafitri, P. R., Widihastuti, & Jerusalem, M. A. (2021). Pewarnaan Alam Daun Ketapang Pada Pada Produk Upcycle Busana Anak. 2“5.